An Effective Non‐Enzymatic Glucose Biosensor Based on Nanostructured CuxO/Cu Electrodes Synthesized in Situ by Copper Anodization. Issue 11 (22nd February 2023) - Wang, Chen; Gao, Nan; Gao, Zhaoqing; Li, Ruofan; Wang, Yunpeng; Gong, Weitao
Abstract: Potentiostatic anodization was developed to synthesize copper oxide/copper (Cux O/Cu, x=1, 2) electrode with nano structure for sensitive non‐enzymatic glucose detection. At a catalytic potential of 0.55 V, the CuO/Cu electrode presented a high sensitivity of 2954.38 μA mM −1  cm −2 to glucose and a linear range of 0.1 mM to 1.3 mM. The response time is less than 3 s with addition of 0.1 mM glucose. The CuO/Cu electrode above was anodized in 1M KOH solution at −100 mV and the morphology was compact nanoparticles and sparsely dispersed nanosheets, which enlarged the surface area and provided abundant electrocatalytic active sites. Compared the sensing property of electrodes with different morphologies, it indicated that nanostructure was significant to the efficient glucose catalytic oxidation process and it could be regulated by changing the potential and electrolyte concentration during anodization. Abstract : CuO/Cu glucose catalytic electrode is fabricated by copper anodization which can construct nanostructure in situ on copper substrates and regulate the chemical composition and morphology of the anodized films. The anodized CuO/Cu sample can be used as catalytic electrode directly and presents a high catalytic performance towards glucose oxidation.